Zebrafish sin3b mutants are viable but have size, skeletal, and locomotor defects. Issue 11 (25th September 2017) - Moravec, Cara E.; Yousef, Hakeem; Kinney, Brian A.; Salerno‐Eichenholz, Ryan; Monestime, Camillia M.; Martin, Benjamin L.; Sirotkin, Howard I.
Abstract : Background: The transcriptional co‐repressor Sin3 is highly conserved from yeast to vertebrates and has multiple roles controlling cell fate, cell cycle progression, and senescence programming. Sin3 proteins recruit histone deacetylases and other chromatin modifying factors to specific loci through interactions with transcription factors including Myc, Rest, p53 and E2F. Most vertebrates have two Sin3 family members ( sin3a and sin3b ), but zebrafish have a second sin3a paralogue. In mice, sin3a and sin3b are essential for embryonic development. Sin3b knockout mice show defects in growth as well as bone and blood differentiation.Results: To study the requirement for Sin3b during development, we disrupted zebrafish sin3b using CRISPR‐Cas9, and studied the effects on early development and locomotor behavior.Conclusions: Surprisingly, Sin3b is not essential in zebrafish. sin3b mutants show a decrease in fitness, small size, changes to locomotor behavior, and delayed bone development. We did not detect a role for Sin3b in cell proliferation. Our analysis of the sin3b mutant revealed a more nuanced requirement for zebrafish Sin3b than would be predicted from analysis of mutants in other species. Developmental Dynamics 246:946–955, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Disruption of zebrafish sin3b reduces fitness but many mutants survive to adulthood and are fertile. Zebrafish sin3b mutants show delayed bone maturation, small size and locomotor defects. Overall cell proliferation rates are not altered by the loss of Sin3b.